2016
DOI: 10.4103/0019-5154.185707
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of two modalities, 4% hydroquinone versus 30% salicylic acid in periorbital hyperpigmentation and assessment of quality of life before and after treatment

Abstract: Background:Periorbital hyperpigmentation (POH) is a common hyperpigmentary problem of the face, which can be psychologically distressing and it can influence an individual's quality of life. However, this condition has received less attention in literature.Aims and Objectives:To study the clinico-etiological features and the effect of two therapeutic modalities on the quality of life in patients of POH before and after treatment.Materials and Methods:Fifty patients attending the outpatient clinic of Dermatolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Another study compared the effect of topical bleaching agent (4% hydroquinone) and 30% salicylic acid peel for 12 weeks, and studied the effect on the quality of life in POH patients in both groups. The authors found that both modalities significantly improved the dermatological life quality index of the patients with no significant difference found between them …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Another study compared the effect of topical bleaching agent (4% hydroquinone) and 30% salicylic acid peel for 12 weeks, and studied the effect on the quality of life in POH patients in both groups. The authors found that both modalities significantly improved the dermatological life quality index of the patients with no significant difference found between them …”
Section: Discussionmentioning
confidence: 92%
“…The authors found that both modalities significantly improved the dermatological life quality index of the patients with no significant difference found between them. 21 Because of its autologous nature, PRP is applied without any serious adverse effects, aside from local injection site reactions like pain or secondary infection, which can be precluded with proper precautions.…”
Section: Re Sultsmentioning
confidence: 99%
“…There are topical, physical, and surgical treatment options. Among topical drugs and methods, sunscreens and peels are widely used [16,17]. Tretinoin, vitamin C, arbutin, and azelaic acid are known to reduce melanin pigmentation [18][19][20][21][22].…”
Section: Treatmentmentioning
confidence: 99%
“…Hydroquinone is one of the most commonly used agents for pigmentation reduction in strengths varying from 2% to 6%. In a study performed in Indian patients, 4% hydroquinone was found to be effective and tolerable to treat periorbital hyperpigmentation 9 …”
Section: Treatment Optionsmentioning
confidence: 99%